Water Turbine Hydraulic Regulating System and Modifications To Meet Grid Stability Requirements - Hrovat, Marko (International Conference Fluid Power 2025: Conference Proceedings, 2025)
Over the past three decades, the hydropower sector has seen major technological advancements, driven by rising global electricity demand, increasing energy prices, and growing awareness of the environmental impacts of conventional power generation. These factors have strengthened the role of renewable energy sources-particularly hydropower-in building sustainable energy systems with lower ecological footprints. Current research focuses on retrofitting and digitalizing existing hydropower infrastructure, developing next-generation hydro and aero-hydrodynamic technologies, and deploying hybrid systems integrated with advanced energy storage solutions. Given the inherent variability of renewable sources, high-capacity storage technologies are essential for enhancing grid stability, frequency regulation, and overall resilience. Furthermore, the development of advanced smart grid architectures is crucial to enable distributed, multi-nodal power generation, improve demand–supply balancing algorithms, and support the seamless integration of small and medium-scale energy producers. Together, these innovations aim to optimize energy efficiency, support decarbonization goals, and ensure a reliable and flexible power supply in the face of evolving energy needs and climate challenges.